THEORETICAL METHODOLOGICAL BASIS OF USING WEB TECHNOLOGIES IN CREATING EDUCATIONAL PLATFORMS IN UZBEKISTAN - Dr. Aman T. Kenjabaev; Master: Lola Boynazarova; Munira Botirova; To'tigul Yusupova (Scholars Digest Publishing, 2024)
The use of distance learning systems and web platforms in the educational process is becoming increasingly important. The article discusses the main tasks of managing the process of teaching students of higher education institutions through remote web platforms to improve the educational process. The current tasks are considered as - creating models for assessing the quality and quantity of management based on modern models of training on remote web platforms and the use of their algorithms and software in the educational process.
Keywords: Web technologies, web platforms, assessment models, algorithms, software, distance learning, educational, electronic and digital resources